(untitled) (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2021)
Translation is an important part of students in learning Arabic, because it will help them in the learning process. But most of them face difficulties when trying to translate reading texts from Arabic to Indonesian. Difficulties of students in translation will hinder the way of achieve a goal of learning. The purpose of this study is to determine the difficulties of students in translating Arabic to Indonesian. The results of this study indicate that the difficulties faced by students include the form of translation difficulties themselves in the form of difficulties in choosing the meaning, form, and rules. And also includes several factors in the form of linguistic, non-linguistic, internal, and external factors.